MR image‐based synthetic CT for IMRT prostate treatment planning and CBCT image‐guided localization. (8th May 2016) - Chen, Shupeng; Quan, Hong; Qin, An; Yee, Seonghwan; Yan, Di
Abstract : The purpose of this study was to propose and evaluate a method of creating a synthetic CT (S‐CT) from MRI simulation for dose calculation and daily CBCT localization. A pair of MR and CT images was obtained in the same day from each of 10 prostate patients. The pair of MR and CT images was preregistered using the deformable image registration (DIR). Using the corresponding displacement vector field (atlas‐DVF), the CT image was deformed to the MR image to create an atlas MR‐CT pair. Regions of interest (ROI) on the atlas MR‐CT pair were delineated and used to create atlas‐ROI masks. 'Leave‐one‐out' test (one pair of MR and CT was used as subject‐MR and subject‐CT for evaluation, and the remaining 9 pairs were in the atlas library) was performed. For a subject‐MR, autosegmentation and DVFs were generated using DIR between the subject‐MR and the 9 atlas‐MRs. An S‐CT was then generated using the corresponding 9 paired atlas‐CTs, the 9 atlas‐DVFs and the corresponding atlas‐ROI masks. The total 10 S‐CTs were evaluated using the Hounsfield unit (HU), the calculated dose distribution, and the auto bony registration to daily CBCT images with respect to the 10 subject‐CTs. HU differences ( mean ± STD ) were ( 2.4 ± 25.23 ), ( 1.18 ± 39.49 ), ( 32.46 ± 81.9 ), ( 0.23 ± 40.13 ), and ( 3.74 ± 144.76 ) for prostate, bladder, rectal wall, soft tissue outside all ROIs, and bone, respectively. The discrepancy of dose‐volume parameters calculated using the S‐CT for treatment planning was small ( ≤ 0.22 % with 95% confidence). Gamma pass rate (2% & 2 mm) was higher than 99.86% inside PTV and 98.45% inside normal structures. Using the 10 S‐CTs as the reference CT for daily CBCT localization achieved the similar results compared to using the subject‐CT. The translational vector differences were within 1.08 mm ( 0.37 ± 0.23 mm ), and the rotational differences were within 1.1° in all three directions. S‐CT created from a simulation MR image using the proposed approach with the preconstructed atlas library can replace the planning CT for dose calculation and daily CBCT image guidance. PACS number(s): 87.57.nf, 87.57.nm